ANALISIS SIMPANG 4 BASUKI RAHMAT - R. SUKAMTO - ANGKATAN 66 - JALAN AMFIBI TERJADINYA MANAJEMEN LALU LINTAS AKURAT SESUDAH PAMBANGUNAN FLYOVER - Aprizal, Ical; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
After conducting research directly in the field on the side of the signalized Simpang Fly Over Sekip, it can be concluded that the average daily traffic volume at the Simpang Sekip Fly Over is 15129 vehicles/hour and 10115.6 SKR/hour and the peak hour volume is 1556 vehicles and 1003 vehicles. This SKR/hour occurs when APIL is on. The largest saturation flow (So) at the Simpang Sekip Flyover intersection occurs at the approach to Jalan Angka 66 at 5760, while the saturation flow along the side is 5184. The intersection capacity, based on the results of research on the capacity of the intersection at peak hours, was found to be 3367 cur/hour. The average degree of saturation value Average (DS), based on research results, the degree of saturation (DJ) at peak hours was found to be 1.56. Queue length (NQ), based on this research, the Simpang Sekip Fly Over intersection is the R. Sukamto intersection which has the longest queue length of 170m. Delay time, the calculation of delays at the busiest hour at the Jalan Amphibi intersection is 21.6 sec/kr and level of service (C) Keywords: Simpang Sekip Fly Over, Daily Traffic